Today's subject: TADs - Riquelmy, Alan (McClatchy - Tribune Business News, 2007)
"Basically, it's a very simple idea," said Kenneth Bleakly, president of the Bleakly Advisory Group. "What changes is that when new development comes in, it pays more taxes," Bleakly said. "You won't even see it on your bill." Some TAD supporters decry the use of the word "tax" in the acronym, calling it a misnomer. Tax money doesn't come from homeowners or shoppers, but instead from future development in the TAD, Bleakly said.